What cool fish live in icy Antarctica? - GERMAN ... - Lopez, Isabel; Postlethwait, John; Desvignes, Thomas (University of Oregon Science and Comics Initiative, 2024)
The Southern Ocean that surrounds Antarctica is one of the coldest on earth and hovers freezing temperatures year-round. What fish can live in such a frigid environment? In this short scientific graphic novel, What cool fish live in icy Antarctica?, Isabel Lopez, John Postlethwait and Thomas Desvignes present the history of Antarctica and how it became the icy continent. These glacial conditions prevented most fish species from living there, but one group, the notothenioids, evolved a way to survive and even thrive in the ice-cold Antarctic waters. They diversified from the surface to the dark depths of the ocean, from being just a few centimeters long to extremely large, and in many other surprising ways. And among them, the white-blooded icefishes are also certainly some of the strangest fish on the planet! But today, Antarctica is changing fast, raising concerns about the survival of these unique fish. Click on the image below to read the graphic novel in English. Or scroll further down to read the ...